The Influence of Taxes , Intangible Assets, Exchange Rates on Transfer Pricing in Multinational Manufacturing Companies Registered on the IDX 2019-2022 - Intan Febrianti; Alimuddin (International Journal of Educational and Life Sciences, 2024)
The aim of this research is to determine the effect of taxes, intangible assets, Exchange Rate on transfer pricing in multinational manufacturing companies listed on the IDX from 2019-2022. This research is a type of quantitative research, namely using secondary data in the form of financial reports owned by the company. Where the sample was determined using a purposive sampling technique so that a sample of 40 samples was obtained. Data was obtained with the help of the SPSS program. The results of this research show that taxes and exchange rates have a negative effect on transfer pricing, while intangible asset variables have a positive effect on transfer pricing.